Pengaruh Motivasi dan Insentif Terhadap Semangat Kerja Karyawan Pada PT. Mujur Timber Sibolga - Cici Anggraini; Fauziah Nur Simamora; Mhd. Shafwan Koto (Universitas Pahlawan Tuanku Tambusai, 2023)
This study entitled the effect of motivation and incentives on morale at PT. Mujur Timber Sibolga The purpose of this study was to determine the effect of motivation and incentives on morale at PT. Good luck Timber. The population in this study is all employees are all employees at PT. Mujur Timber Sibolga, which has a total of 525 employees. The sample in this study used a side random chuster method consisting of 53 employees. Primary data collection was carried out through questionnaires, where before the questionnaires were distributed, validity and reliability tests were first carried out on the questionnaires. The analytical method used in this research is descriptive analysis method and quantitative analysis, namely by multiple linear regression analysis. Data processing was carried out using the SPSS Statistics 20 program for windows. The results showed that all data included in the model were normally distributed as shown by the histogram graph in the form of a bell and the normal graph of the PP Plot Standardized residual showing all the residual data points of the three variables following the diagonal line data on the scatter plot and the Kolmogorov Smrinov statistical test showing the value z 0.682 < from Z α 5% which is 1.97 and the probability value is 0.741> 0.05. Heteroscedasticity and multicollinearity problems are not found in the model, which is shown by the dots spreading randomly and both above and below zero on the Y axis. The tolerance values ​​of each independent variable are 0.659 and 0.659 above 0.1 and the variance inflation factor values ​​are 1.517 and 1.517 does not exceed 10. The results of the social hypothesis test show that motivation has a positive and significant effect on morale at PT. Luckily, Timber Sibolga has proven that t count is 5.049 > t table is 0.68 and a probability value is 0.000 < α 0.05. Incentives have a positive and significant effect on morale because t count is 3.744 <0.68 and the probability value is 0.000 > α 0.05. Simultaneously test the hypothesis where F count is 46.684> F table is 4.034 and the probability value is 0.000 <α 0.05. Keywords: motivation, incentives and morale